Heat responsive gene StGATA2 functions in plant growth, photosynthesis and antioxidant defense under heat stress conditions - Zhu, Xi; Duan, Huimin; Jin, Hui; Chen, Shu; Chen, Zhuo; Shao, Shunwei; Tang, Jinghua; Zhang, Yu (Frontiers in Plant Science, 2023)
Backgrounds: Potato is sensitive to heat stress particularly during plant seedling growth. However, limited studies have characterized the expression pattern of the StGATA family genes under heat stress and lacked validation of its function in potato plants. Methods: Potato plants were cultivated at 30oC and 35oC to induce heat stress responses. qRT-PCR was carried out to characterize the expression pattern of StGATA family genes in potato plants subjected to heat stress. StGATA2 loss-of-function and gain-of-function plants were established. Morphological phenotypes and growth were indicated by plant height and mass. Photosynthesis and transpiration were suggested by stomatal aperture, net photosynthetic rate, transpiration rate, and stomatal conductance. Biochemical and genetic responses were indicated by enzyme activity and mRNA expression of genes encoding CAT, SOD, and POD, and contents of H2O2, MDA, and proline. Results: The expression patterns of StGATA family genes were altered in response to heat stress. StGATA2 protein located in the nucleus. StGATA2 is implicated in regulating plant height and weight of potato plants in response to heat stresses, especially acute heat stress. StGATA2 over-expression promoted photosynthesis while inhibited transpiration under heat stress. StGATA2 overexpression induced biochemical responses of potato plant against heat stress by regulating the contents of H2O2, MDA and proline and the activity of CAT, SOD and POD. StGATA2 overexpression caused genetic responses (CAT, SOD and POD) of potato plant against heat stress. Conclusions: Our data indicated that StGATA2 could enhance the ability of potato plants to resist heat stress-induced damages, which may provide an effective strategy to engineer potato plants for better adaptability to adverse heat stress conditions.